The correlation between Life’s essential 8 and cardiovascular disease and mortality in individuals with nonalcoholic fatty liver disease: a cross-sectional study - Sun, Meng; Qiu, Yong; Zhang, Lei; Chen, Guo (Scientific reports, 2024)
It is currently unclear whether there is a connection between Life’s Essential 8 (LE8) and cardiovascular disease (CVD), as well as mortality in people with nonalcoholic fatty liver disease (NAFLD). Our goal was to explore these relationships by examining data collected in the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018. We identified eligible participants with NAFLD based on NHANES 2005–2018 data. CVD status was acquired through self-reported information, and using the National Death Index, mortality data were prospectively matched. The diagnosis of NAFLD relied on noninvasive biomarkers. The research involved 9094 individuals who were identified as having NAFLD, with a mean age of 52.05 years. Each incremental LE8 score exhibited a significant association, leading to a 3%, 3%, 4%, 3%, 3%, 4%, and 4% reduction in the odds of experiencing CVD, ischemic heart disease, congestive heart failure, coronary heart disease, heart attack, angina, and stroke in individuals with NAFLD. A strong correlation was found between maintaining a superior level of Cardiovascular Health (CVH), as shown by a LE8 score ranging from 80 to 100, and a reduced occurrence of CVD and its various forms in NAFLD (all p for trend < 0.0001). Likewise, LE8 demonstrated protective benefits on mortality in NAFLD, showing that following a high CVH (in contrast to low CVH) was linked to reductions of 64%, 71%, and 74% in all-cause, CVD, and cancer mortality, respectively. Restricted cubic spline analyses suggested noteworthy dose-response relationships between LE8 and CVD, specifically its types in NAFLD, and a nonlinear correlation with CVD mortality. Interaction analyses highlighted age and race as significant effect modifiers. CVH, as evaluated by LE8, demonstrated an independent association with decreased odds of CVD and mortality risk in individuals with NAFLD. Our findings substantiate that adhering to LE8 may alleviate the excessive burden of CVD and mortality in the context of NAFLD.